Sarjana Nantah dan peranannya dalam pengembangan bahasa dan sastera Melayu - Chong, Fah Hing (Universiti Kebangsaan Malaysia, 2003)
The establishment of Nanyang University (Nantah) was seen to be more destructive than constructive in the eyes of colonial masters and others, because the timing coincided with the political whirlwind surrounding the development of national identity in Singapore and Malaysia. That scenario interestingly aroused a keen interest among the students of Nantah in learning Malay language and literature. As a result, several respectful scholars and researchers in these two fields appeared. Nevertheless, their contributions and roles have seldom been publicized in the academic discourse on Malay world studies until now. This article attempts not only to review the scholarship of two prominent figures from Nantah in moulding the understanding and opinion of the Chinese community about Malay language and literature, but also to summarize the characteristics they shared in their involvement